A permanent state of sanctions? Proposal for a more flexible EU sanctions policy toward Russia - Sabine Fischer (Stiftung Wissenschaft und Politik (SWP), 2017)
Sanctions seem to have become a permanent element in relations between the EU and Russia. They have contributed to curbing the war in Donbas but are not capable of forcing Russia to return Crimea to Ukraine and implement the Minsk agreements. In 2017, consensus within the EU on sanctions against Russia is more fragile than it has been previously. As a result, therefore, the EU needs to consider now what strategic steps it should take next. (SWP Comments)
Keywords: 320